A molecular mechanism for IL-4 suppression of loricrin transcription in epidermal keratinocytes: implication for atopic dermatitis pathogenesis. Issue 8 (November 2017) - Bao, Lei; Mohan, Girish C; Alexander, Jaime B; Doo, Caroline; Shen, Kui; Bao, Jeremy; Chan, Lawrence S
Skin barrier defects play an important role in atopic dermatitis (AD) pathogenesis. Loricrin, an important barrier protein suppressed in human AD, is down-regulated by IL-4 in keratinocytes. However, the molecular mechanism is unknown. Since loricrin transcription requires p300/CBP, and Stat6 also recruits this common coactivator for its stimulated factors, we hypothesize that IL-4-activated Stat6 competes for the available endogenous p300/CBP, leading to loricrin transcription inhibition. First, we showed that loricrin is suppressed in the skin of IL-4 transgenic mice, an AD mouse model. In human keratinocytes, IL-4 down-regulation of loricrin is abrogated by a pan-Jak inhibitor, suggesting that the Jak-Stat pathway is involved. To further investigate the downstream molecular mechanism, we transfected HaCat cells with a loricrin promoter and then treated them with either IL-4 or vehicle. Not surprisingly, IL-4 greatly suppressed the promoter activity. Interestingly, this suppression was prevented when we knocked down Stat6, indicating that Stat6 participates in IL-4 regulation of loricrin. A Stat6-specific inhibitor confirmed the knockdown study. Finally, IL-4 suppression of loricrin was reversed with transfection of a CBP expression vector in a dose-dependent manner. Taken together, for the first time, we delineate a molecular mechanism for IL-4 down-regulation of loricin expression in human keratinocytes, which may play an important role in AD pathogenesis.